2015
DOI: 10.1017/s026505171500011x
|View full text |Cite
|
Sign up to set email alerts
|

Communities of practice in the conservatory: learning with a professional musician

Abstract: This article examines the sociocultural learning of popular and jazz music in communities of practice as part of secondary vocational music education in a Finnish conservatory. The research is based on performance workshops which were implemented as a joint effort between professional musicians and music students. These workshops are suggested as a method of utilising communities of practice. Research outcomes show that the workshops include opportunities for learning and developing musicianship on many levels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(41 citation statements)
references
References 67 publications
1
38
0
2
Order By: Relevance
“…These informal group practices contrast with those of the conservatoire, where one-to-one tuition is the predominant educational model for music practice and performance (Bjøntegaard, 2015;Carey & Grant, 2015;Virkkula, 2016b;Gaunt, 2017). Informal pedagogies within communities of practice have much to recommend themselves in arts education (Virkkula, 2016a), and more specifically, it is argued in this paper, within HME (see also Westerlund & Partti, 2012). This article explores some of the ways in which collaborative learning might broadly inform pedagogies of music practice within HME (see also Hanken, 2016).…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…These informal group practices contrast with those of the conservatoire, where one-to-one tuition is the predominant educational model for music practice and performance (Bjøntegaard, 2015;Carey & Grant, 2015;Virkkula, 2016b;Gaunt, 2017). Informal pedagogies within communities of practice have much to recommend themselves in arts education (Virkkula, 2016a), and more specifically, it is argued in this paper, within HME (see also Westerlund & Partti, 2012). This article explores some of the ways in which collaborative learning might broadly inform pedagogies of music practice within HME (see also Hanken, 2016).…”
Section: Introductionmentioning
confidence: 95%
“…Collaborative learning for popular music practice and performance draws on informal learning processes ranging from the garage band (Westerlund, 2006) through to the practices of professional popular musicians (e.g. Virkkula, 2016a). When collaborative learning is used for music practice and performance, masters and apprentices become co-constructors of learning (Lave & Wenger, 1991;Lebler, 2007;Hanley, Baker, & Pavlidis, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This research is a continuation of an earlier workshop project from the perspective of sociocultural learning in communities of practice (Virkkula 2016a). The previous research results showed that the workshop corresponds to the features of community of practice.…”
Section: Research Contextmentioning
confidence: 65%
“…Collaborative learning within intensive workshops has been explored. For example, situated and collaborative learning experienced within jazz and popular music conservatoire performance workshops was investigated by Virkkula ( 2016 ). Using a case study approach and gathering data via students' reflective journal entries, Virkkula investigated the processes of sociocultural learning within workshops structured as communities of musical practice comprising students and professional musicians.…”
Section: Resultsmentioning
confidence: 99%